A grinder for groundnuts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The Electra Company' which specializes in tropical product packaging, has just developed a groundnut grinder. This machine grinds shelIed groundnuts into a smooth homogeneous paste. It can work continuously either from the mains or with petrol and...